Are rises in Electro-Magnetic Field in the human environment, interacting with multiple environmental pollutions, the tipping point for increases in neurological deaths in the Western World?. (June 2019) - Pritchard, Colin; Silk, Anne; Hansen, Lars
Abstract: Whilst humans evolved in the earth's Electro-Magnetic-Field (EMF) and sun-light, both being essential to life but too much sun and we burn. What happens if background EMF rise to critical levels, coinciding with increasing environmental pollutants? Two of the authors can look back over 50 clinical years and appreciate the profound changes in human morbidity across a range of disparate conditions – autoimmune diseases, asthma, earlier cancer incidence and reduced male sperm counts. In particular have been increased autism, dyslexia, Attention Deficit Hyperactivity Disorder and neurological diseases, such as Amyotrophic Lateral Sclerosis, Multiple Sclerosis, Parkinson's Disease, Early Onset Dementia, Multiple System Atrophy and Progressive Supranuclear Palsy. What might have caused these changes-whilst genetic factors are taken as given, multiple environmental pollutants are associated with neurological disease although the mechanisms are unclear. The pace of increased neurological deaths far exceeds any Gompertzian explanation - that because people are living longer they are more likely to develop more age-related problems such as neurological disease. Using WHO global mortality categories of Neurological Disease Deaths (NDD) and Alzheimer's and Dementia deaths (Alz), updated June 2018, together they constitute Total Neurological Mortality (TNM), to calculate mortality rates per million for people aged 55–74 and for the over-75's in twenty-one Western countries. Recent increases in American people aged over-75's rose 49% from 1989 to 2015 but US neurological deaths increased five-fold. In 1989 based on Age-Standardised-Deaths-Rates America USA was 17th at 324 pm but rising to 539 pm became second highest. Different environmental/occupational factors have been found to be associated with neuro-degenerative diseases, including background EMF. We briefly explore how levels of EMF interact upon the human body, which can be described as a natural antennae and provide new evidence that builds upon earlier research to propose the following hypothesis. Based upon recent and new evidence we hypothesise that a major contribution for the relative sudden upsurge in neurological morbidity in the Western world (1989–2015), is because of increased background EMF that has become the tipping point-impacting upon any genetic predisposition, increasing multiple-interactive pollutants, such as rises in petro-chemicals, hormone disrupting chemicals, industrial, agricultural and domestic chemicals. The unprecedented neurological death rates, all within just twenty-five years, demand a re-examination of long-term EMF safety related to the increasing background EMF on human health. We do not wish to 'stop the modern world', only make it safer.